Risk and risk weights - Søren Korsgaard (Danmarks Nationalbank, 2019)
This paper studies the relationship between the riskiness of banks' assets and their average risk weight. Banks' initial risk weights explain about half of the variation in projected credit losses in the 2018 European Banking Authority stress test. In contrast to related papers, this paper also shows a statistically and economically significant relationship between risk weights and estimates of banks' asset volatilities based on market data. However, I also find issues with risk weights as measures of risk. They do a worse job of explaining future credit losses than do asset volatilities, especially in the case of banks using internal models.
Keywords: G20; G28; 330; Financial regulation; stress tests; credit risk